OPTIMALISASI PELAYANAN KESEHATAN TERHADAP MASYARAKAT MISKIN DI PROVINSI GORONTALO - Harson Gasim (Publik : (Jurnal Ilmu Administrasi), 2015)
The main problems of the current health services among others are still high disparity between the health status of the population had a high socioeconomic level of the population has a low socioeconomic level or poor. Low health status of the poor is closely related to limited access to health care, either because of geographical constraints or cost constraints (cost barrier). In other words, that the biggest obstacle facing the poor people to obtain health care facilities is the lack of cost, distance to health care facilities are too far away, as well as barriers to the means of transport or transport. To that end the Provincial Government through the Department of Health has Goorntalo optimizing health care for the poor with concrete actions such as (1) Equity in health services for the poor through the placement of doctors and paramedics, especially in health centers and hospitals in underdeveloped areas; increase the availability, equity, quality, and affordability of drugs and medical supplies, especially for the poor; and improving the quality of community pharmacy services and hospitals; (2) Improving the equity and affordability of health care; (3) Improve the quality of health services; (4) Improving hygienic behavior and healthy; (5) Improving the prevention and eradication of disease; (6) Improving the nutritional state of society; (7) Improving the handling of health problems in the affected areas.